Uncontrolled risk the lessons of Lehman Brothers and how systemic risk can still bring down the world financial system - Williams, Mark T. 1963- (McGraw-Hill, 2010)
A risk advisor for top financial institutions explains how limitless risky behaviors toppled a 158-year-old institution, using the story to illuminate the interconnection of the global financial system, as well as broader policy implications
Includes bibliographical references (p. 231-240) and index
Keywords: Lehman Brothers (1993-2008); Lehman Brothers -- 1994-2008; Geschichte; Global Financial Crisis, 2008-2009; Financial crises / United States / History / 21st century; Financial risk; Financial crises / United States / History; Risk; Risiko; Investment Banking; Finanzkrise; USA